Review of J. Ronald Engel's Sacred sands: the struggle for community in the Indiana Dunes - Rolston, Holmes, 1932-2025, author; Joint Publication Board of Zygon, publisher (Colorado State University. Libraries, 1984)
Sacred Sands is a welcome contribution to religious studies, environmental ethics, and American history. Ron Engel narrates the bitterly contested struggle to save the Indiana Dunes on Lake Michigan. This is a story of the people of Chicago and their landscape with moral vision for Americans and their landscapes everywhere.
This is an electronic version of an article published in Zygon®: Journal of Religion and Science.
Keywords: Indiana Dunes; Chicago; environmental conservation; environmental ethics; sacred nature; Lake Michigan